A New Role for Transport in the Development of the Sustainable City of the Future - Thisgaard, Preben (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
Sustainability, fundamental values and possibilities of Scandinavian society are explored. The unique possibilities of the transport sector to form the spearhead of development of a sustainable society are explained. The principle of a fusion between the academic disciplines of economy and ecology is investigated. A number of development possibilities in the field of "sustainable mobility" are pointed out. Such a development will hardly lead to a successful result or contain any real substance unless the transport sector leaves its present isolation behind and take active part in the development of a new model of society where transport is a link in a chain of actions and services forming a holistic point of view not threatening the survival of coming generations or their basic quality of life.